Drosophila melanogaster (Diptera: Drosophilidae): biological model to define the standarization of natural extracts with activity insecticide (the neem -Azadirachta indica - a particular case) - MORENO, MARIA EUGENIA; GONZÁLEZ, SANTIAGO; ACEVEDO, LILIANA; MORALES, GLADYS; BETANCUR, MONICA; LÓPEZ, JHON JAIRO; PELÁEZ, CARLOS ALBERTO (Revista Colombiana de Entomología, 2000)
This paper shows the use of the biological model Drosophila Melanogaster on the quantification of the insecticide activity of neem extracts. HPLC profiles were determined for the alcohol and ether fractions. The quality and quantity of the metabolites found in both fractions showed significant differences. Fractions of different polarities were tested with the biological model observing a correlation between the inhibition for the puparium-adult change and the increase in the polarity of the neem fraction. The same biological model was used to study the kinetic for the alcohol and ether fractions of the neem extract. The alcohol extract showed stability up to 6 months at 20ºC, 80% humidity, and dark conditions. Finally, the Drosophila Melanogaster model was used for a comparative study of the biological activity between different commercial neem extracts.